Coke Formation over a Nickel Catalyst under Methane Dry Reforming Conditions: Thermodynamic and Kinetic Models - Ginsburg, Jason M. (2005)
The CO2 reforming of methane is studied over a 20 wt% Ni/USY-zeolite, and more specifically, a thermodynamic analysis of the formation of coke is used as a basis for the kinetic modeling of coke phenomena that exist under dry reforming conditions. Two thermodynamic parameters, α and β, are compared to the equilibrium constants for the CH 4 decomposition and the CO disproportionation reactions and defined to determine whether coke formation is favored. This thermodynamic analysis elucidates the significance of the CO disproportionation reaction on the amount of coke deposited over the catalyst under consideration. A kinetic model with negative overall order of one, with respect to the partial pressure of carbon monoxide, is found as the most accurate prediction of the rate of coke formation. This type of kinetics strongly suggests the requirement of three adjacent free catalyst sites for the coking reaction to proceed under allowable thermodynamic conditions.